Методичні особливості вивчення реактивності капсули суглоба - Григор'єва, Олена Анатоліївна; Григорьева, Е. А.; Grygorieva, O. A. (Полтава: УМСА, 2015)
Резюме. В роботі надано алгоритм гістологічного вивчення морфогенезу і реактивності капсули суглобу, який дозволяє визначити ступень реактивності всіх компонентів суглобової капсули. Запропонований алгоритм супроводжується результатами вивчення реактивності капсули суглоба в експериментальних умовах (внутрішньо плідне введення антигену). Резюме. В работе приводится обоснованный алгоритм гистологического исследования морфогенеза и реактивности суставной капсулы, позволяющий оценить степень реактивности всех компонентов капсулы сустава. Предложенный алгоритм сопровождается результатами изучения реактивности капсулы сустава в эксперименте на лабораторных животных (внутриплодное введение антигена). Abstract. Articular capsule is an important integral part of the joint, it provides maintenance of joint integrity. Different capsule’s impairments lead to the development of joint diseases, which may cause disability and even patient’s invalidation especially if we discuss impairment of a hip or a knee joint. The great number of works is devoted to the morphological researches of joint capsule in adult patients with joint diseases. The investigation of joint capsule in newborns that were undergone different harmful influences during intranatal period are worth carrying out in order to define a morphological background of different joint diseases. Nowadays, the exact algorithm of joint capsule reactivity investigation is absent. That is why different unclear spots remain; that complicates the understanding of the problem by specialists of different areas (clinical investigators and laboratory (morphological) researchers). The purpose of the work is to define and substantiate methods of morphological investigation of a joint capsule reactivity. Methods. In the first place, while conducting histological investigation it is necessary to determine common histological terms of different layers and parts of articular capsule according to the modern anatomical and histological nomenclatures. It is proposed to define fibrous and synovial layers of joint capsule, visceral, parietal and intermediate parts of synovial layer. In the second place, while discussing the process of capsule’s reactivity it is necessary to define interaction between its compounds: microcirculatory vessels, fibers, cells and extracellular matrix. For this purpose it is possible to use Mallory, Van Hyson reactions, impregnation of histological samples with argentum carbonate or nitrate, etc. In the third place, it is obvious analysis of lymphocytes and dendritic cells population. In the fourth place – the analysis of mast cells population. In the fifth place – the analysis of proliferative activity. And after all, it is perfectly necessary to use modern adequate statistical analysis. Results. The reactivity of newborns’ knee joint capsule after intranatal antigen injection was investigated in the work with the help of proposed algorithm. The analysis of obtained data gave total integral illustration of joint capsule morphogenesis and reactivity after intranatal antigen injection.
Методические особенности изучения реактивности капсулы сустава
Methodical peculiarities of joint capsule reactivity investigation
Keywords: капсула суглоба; реактивність; синовіальний слой; судини мікроциркуляторного русла; лімфоцити; капсула сустава; реактивность; синовиальный слой; сосуды микроциркуляторного русла; лимфоциты; joint capsule; reactivity; synovial layer; microcirculatory vessels; lymphocytes